Evaluasi Pengalaman Pengguna Aplikasi Access by KAI Menggunakan Metode UX Honeycomb - Solikha, Nur Imroatus; Faroqi, Asif; Wulansari, Anita (STMIK Banjarbaru, 2024)
Access by KAI is a train ticket booking application released by PT Kereta Api Indonesia as a modern alternative for the community with innovative features that make train travel easier. However, there are indications of poor user experience supported by many reviews on the play store and app store that show user dissatisfaction in using the access by KAI application. This study aims to evaluate the user experience of Access by KAI using the UX Honeycomb method which has seven aspects including useful, usable, desirable, findable, accessible, credible, and valuable with a sample of 524 Access by KAI user respondents in the Javaisland area. Referring to the results of hypothesis testing, it is found that the Feel, Think, and Use variables significantly affect the User Experience variable Translated with DeepL.com (free version).Keywords: Access by KAI; User experience evaluation; UX honeycombÂ AbstrakAccess by KAI merupakan aplikasi pemesanan tiket kereta api yang dirilis oleh PT Kereta Api Indonesia sebagai alternatif modern untuk masyarakat dengan fitur inovatif yang memudahkan perjalanan kereta api. Akan tetapi, terdapat indikasi pengalaman pengguna yang buruk didukung oleh banyak ulasan pada play store dan app store yang menunjukkan ketidakpuasan pengguna dalam menggunakan aplikasi access by KAI. Penelitian ini bertujuan untuk mengevaluasi pengalaman pengguna Access by KAI menggunakan metode UX Honeycomb yang memiliki tujuh aspek meliputi useful, usable, desirable, findable, accessible, credible, dan valuable dengan sampel 524 responden pengguna Access by KAI di wilayah pulau Jawa. Mengacu pada hasil pengujian hipotesis didapatkan hasil bahwa variabel Feel, Think, dan Use secara signifikan mempengaruhi variabel User Experience.Â